Developing Student’s Speaking Skill Based On Aivideo at Senior High School Grade X SMK Yayasan Taruna Bangsa Sawit Seberang 2024/2025 - Febriana, Dwi Intan; Risnawaty; Asnawi (PT Inovasi Pratama Internasional, 2026)
This study aims to produce AI-based learning video media that can be used to improve the speaking skills of tenth-grade students at SMK Yayasan Taruna Bangsa Sawit Seberang. This research is a research and development (R&D)study using the ADDIE model, which consists of five stages. The trial subjects included media experts, material experts, and learning experts. The object of the study was the developed AI-based learning video. Data collection was conducted through a validation questionnaire administered to the expert validators. The results showed that the learning media received a validity score of 83 from the media experts, 94 from the material experts, and 92 from the learning experts, all of which fall into the